Depletion of mitochondrial reactive oxygen species downregulates epithelial-to-mesenchymal transition in cervical cancer cells - Shagieva, Galina (Oncotarget, 2016)
In the course of cancer progression, epithelial cells often acquire morphological and functional characteristics of mesenchymal cells, a process known as epithelial-to-mesenchymal transition (EMT). EMT provides epithelial cells with migratory, invasive, and stem cell capabilities. Reactive oxygen species produced by mitochondria (mtROS) could be of special importance for pro-tumorigenic signaling and EMT. In our study, we used mitochondria-targeted antioxidant SkQ1 to lower the mtROS level and analyze their role in the regulation of the actin cytoskeleton, adhesion junctions, and signaling pathways critical for tumorigenesis of cervical carcinomas. A decrease in mtROS was found to induce formation of β-cytoplasmic actin stress fibers and circumferential rings in cervical cancer SiHa and Ca-Ski cells. It was accompanied by an upregulation of E-cadherin in SiHa cells and a downregulation of N-cadherin in Ca-Ski cells. In SiHa cells, an increase in E-cadherin expression was accompanied by a reduction of Snail, E-cadherin negative regulator. A stimulation of mtROS by epidermal growth factor (EGF) caused a Snail upregulation in SiHa cells that could be downregulated by SkQ1. SkQ1 caused a decrease in activation of extracellular-signal-regulated kinases 1 and 2 (ERK1/2) in SiHa and Ca-Ski. EGF produced an opposite effect. Incubation with SkQ1 suppressed EGF-induced p-ERK1/2 upregulation in SiHa, but not in Ca-Ski cells. Thus, we showed that scavenging of mtROS by SkQ1 initiated reversal of EMT and suppressed proliferation of cervical cancer cells.